Multimedia Development of Student Discipline Character Training at Police Schools Pontianak State - Sugiyono, Sugiyono; Aunurahman, Aunurahman; Astuti, Indri (Sinkron : jurnal dan penelitian teknik informatika, 2021)
This research refers to the design of research and development (R&D), meaning the research method used to produce the product and then test the effectiveness of the product. According to Borg and Gall (2003: 569), the design used in this study was using the design of the ADDIE learning model. These researches have proposed an integrated model between ADDIE learning designs to address their weaknesses, and leverage their strengths in guiding the process of developing training multimedia content for learning, which requires incorporatingthe needs of thetraining pe at the design stage. In this development research data collection instrument using observation teknik with observation sheet tool,. The data analysis used in this study is qualitative and quantitative. Qualitative data analysisin this study willbe conducted to find out from validation experts on the design of student discipline character training at pontianak state police school (SPN). Quantitativedata analysis techniques to find out how validation results from experts or validators against multimedia character training of quantitatively analyzed student disciplines. Quantitative data analysis techniques are carried out to find out how the results of validation from experts on the quality of multimedia training that has been designed and tested with students. The result of this study is the effectiveness of learning is the level of success that can be achieved from a particular learning method in accordance with the learning objectives that have been planned. And this can also be interpreted that a learning medium can be said to be effective when meeting criteria, achieving goals, including being able to provide influence, change or can bring results, then effectiveness can be seen from how far the goal is achieved. The more goals achieved, the more effective the multimedia training is used.